The Arabidopsis heat‐intolerant 5 (hit5)/enhanced response to aba 1 (era1) mutant reveals the crucial role of protein farnesylation in plant responses to heat stress. Issue 3 (27th September 2016) - Wu, Jia‐Rong; Wang, Lian‐Chin; Lin, Yu‐Ru; Weng, Chi‐Pei; Yeh, Ching‐Hui; Wu, Shaw‐Jye
Summary: Protein farnesylation is a post‐translational modification known to regulate abscisic acid (ABA)‐mediated drought tolerance in plants. However, it is unclear whether and to what extent protein farnesylation affects plant tolerance to high‐temperature conditions. The Arabidopsis heat‐intolerant 5 ( hit5 ) mutant was isolated because it was thermosensitive to prolonged heat incubation at 37°C for 4 d but thermotolerant to sudden heat shock at 44°C for 40 min. Map‐based cloning revealed that HIT5 encodes the β‐subunit of the protein farnesyltransferase. hit5 was crossed with the aba‐insensitive 3 ( abi3 ) mutant, the aba‐deficient 3 ( aba3 ) mutant, and the heat shock protein 101 ( hsp101 ) mutant, to characterize the HIT5‐ mediated heat stress response. hit5/abi3 and hit5/aba3 double mutants had the same temperature‐dependent phenotypes as hit5 . Additionally, exogenous supplementation of neither ABA nor the ABA synthesis inhibitor fluridone altered the temperature‐dependent phenotypes of hit5 . The hit5/hsp101 double mutant was still sensitive to prolonged heat incubation, yet its ability to tolerate sudden heat shock was lost. The results suggest that protein farnesylation either positively or negatively affects the ability of plants to survive heat stress, depending on the intensity and duration of high‐temperature exposure, in an ABA‐independent manner. HSP101 is involved in the hit5 ‐derived heat shock tolerance phenotype.